L-Borneol induces transient opening of the blood–brain barrier and enhances the therapeutic effect of cisplatin. Issue 9 (14th June 2017) - Yin, Yi; Cao, Liu; Ge, Hongfei; Duanmu, Wangsheng; Tan, Liang; Yuan, Jichao; Tunan, Chen; Li, Fei; Hu, Rong; Gao, Fabao; Feng, Hua
Abstract : The blood–brain barrier (BBB) protects the central nervous system from external insults by limiting substance diffusion through the endothelial interface. The presence of the BBB makes drug delivery in neurological disorders very challenging. Cisplatin has been shown to be cytotoxic to glioma cells, but substantial limitations exist in its clinical applications due to difficulties in penetration across the BBB. Here, we show that L-borneol, a messenger drug widely used in traditional Chinese medicine, can induce transient disruption of the BBB after 20 min of oral administration. The permeability of the BBB began to recover within 1 h of the administration of L-borneol. Different dosages of L-borneol (100, 150, 300, 600, and 900 mg/kg) could induce significant Evans blue leakage ( P <0.05). Oral administration of L-borneol elevated cisplatin concentrations in peritumoral tissue (1.24±0.12 μg/g) and tumor loci (1.41±0.13 μg/g), compared with those in the paraffin control (0.88±0.10 and 0.92±0.15 μg/g, respectively) ( P <0.05). Furthermore, we found that the median survival period of tumor-bearing mice was significantly higher in the cisplatin plus L-borneol group (24.0±4.9 days) than in the cisplatin plus vehicle group (19.3±3.9 days) ( P <0.05). The neurological deficits were more severe in the vehicle and cisplatin plus vehicle groups at 14 and 21 days after implantation of intracranial glioma cells than in the cisplatin plus L-borneol group. In conclusion, our results indicate that the transient opening of the BBB induced by L-borneol could enhance cisplatin accumulation within the glioma tissue and improve the survival of tumor-bearing mice.